Uji Aktivitas Antibakteri pada Karang Lunak Villogorgia dari Pulau Ketawai, Bangka Tengah, terhadap Dua Jenis Bakteri Penyebab Penyakit Kulit (Pseudomonas aeruginosa dan Staphylococcus aureus) - Siska Anggraini; Mu’alimah Hudatwi; La Ode Wahidin (JURNAL ENGGANO, 2026)
Indonesia has quite extensive waters and abundant natural resources with the highest diversity of coral reefs. The high diversity of coral reefs makes several areas dependent on this area. The rapid advances in technology today mean that many marine organisms have metabolite compounds that are used as medicinal ingredients, which come from animals, plants or bacteria in the sea, one of which is the gorgonian organism. The aim of this research is to determine whether the gorgonian organism can be an antimicrobial agent against bacteria that cause skin diseases (Pseudomonas aeruginosa and Staphylococcus aureus) and the difference in sensitivity of the two bacteria. This research was conducted in December 2023 - February 2024. The gorgonia samples used were taken in the waters of Ketawai Island using a random sampling method. Then an antibacterial test was analyzed and carried out using the Kirby-Bauer disc diffusion method at the Biology Laboratory of Bangka Belitung University. After obtaining the results of the inhibition zone from the antibacterial test, a descriptive analysis was carried out by looking at the categories from the provisions of David and Stout 1971. The research results showed that the gorgonia type Plexauridae can be an antibacterial agent with an average zone of inhibition of 6,80 mm for Pseudomonas aeruginosa bacteria, 2,90 mm for Staphylococcus aureus bacteria. The sensitivity obtained was different in the two test bacteria with different average values of the inhibition zone but fell into the same category, namely resistant. Keywords: Antibacterial Test, Gorgonia, Ketawai Island, Kirby-Bauer Disc Diffusion, Random Sampling